Synovial Sarcoma Microvesicles Harbor the SYT-SSX Fusion Gene Transcript: Comparison of Different Methods of Detection and Implications in Biomarker Research - A. Fricke; P. V. Ullrich; A. F. V. Cimniak; M. Follo; S. Nestel; B. Heimrich; I. Nazarenko; G. B. Stark; H. Bannasch; D. Braig; S. U. Eisenhardt (Hindawi Limited, 2016)
Background. Synovial sarcoma is an aggressive soft-tissue malignancy. This study examines the presence of the SYT-SSX fusion transcript in synovial sarcoma microvesicles as well as its potential role as a biomarker for synovial sarcoma. Patients and Methods. Microvesicle release of synovial sarcoma cells was examined by transmission electron microscopy. RNA-content was analyzed by qPCR, nested PCR, nested qPCR, and droplet digital PCR to compare their sensitivity for detection of the SYT-SSX fusion gene transcript. Whole blood RNA, RNA of mononuclear cells, and microvesicle RNA of synovial sarcoma patients were analyzed for the presence of the fusion gene transcripts. Results. Electron microscopic analysis revealed synovial sarcoma cells releasing membrane-enclosed microvesicles. In vitro, the SYT-SSX fusion gene transcript was detected in both synovial sarcoma cells and microvesicles. Nested qPCR proved to be the most sensitive in detecting the SYT-SSX fusion gene mRNA. In contrast, the fusion gene transcript was not detected in peripheral blood cells and microvesicles of synovial sarcoma patients. Conclusion. Synovial sarcoma cells release microvesicles harboring the SYT-SSX fusion transcript. Nested qPCR proved to be the most sensitive in detecting the SYT-SSX fusion gene mRNA; however, more sensitive assays are needed to detect cancer-specific microvesicles in the peripheral blood of cancer patients.